Knowledge production in organizations : a processual autopoietic view - Koskinen, Kaj U. (Springer International Publishing, 2013)
The systemic view provides a basic approach through which people may advance their understanding of knowledge production in organizations. One of the most important contributions to this systemic view is the theory of social autopoiesis which emphasizes that knowledge production of organizations can only be understood through the view of a social autopoietic system. Recent developments in the field of organization research have started to view organization as a process rather than as entity. The author combines in this book these two approaches - autopoietic systemic view and process thinking - in a way that organizations are seen as processual autopoietic systems.